Do women with menorrhagia need iron?. Issue 6323 (17th April 1982) - Lewis, G J
Abstract : Haematological indices of iron deficiency and serum ferritin concentrations were compared in 42 women complaining of menorrhagia and in 34 with normal menstrual loss. No significant differences in haemoglobin concentration, mean corpuscular volume, or mean corpuscular haemoglobin concentration were found between the two groups. Serum ferritin concentrations were significantly lower (p less than 0.001) in patients with menorrhagia. Though the iron stores in these women were significantly reduced, only a few were anaemic. Thus, women complaining of heavy menstrual loss do not require prophylactic iron supplements.